LAS REDES SOCIALES VIRTUALES COMO ESPACIOS DE OCIO DIGITAL - Ana VIÑALS BLANCO (Fonseca, Journal of Communication, 2023)
We live in a digital society where habits and lifestyles have been transformed by the development of the Internet and New Technologies of Information and Communication (ICT). Leisure, understood in this article as an experience of human development (Cuenca, 2000) and vital area, neither has resisted the influence of technology and the virtual sphere, and that caused the generation of new virtual leisures, among which the most important is the use of social networks.